Histórias do Turnen na Leopoldenser Turnverein (Sociedade de Ginástica de São Leopoldo) - Levien, Ana Luiza Angelo (2011)
The present work is characterized as a historical research which aimed at systematizing, building and narrating some historical events produced by the Turnen, at the Sociedade de Ginástica de São Leopoldo (SGSL São Leopoldo Gymnastics Society), RS. The research had as its meaningful time the foundation of such Society, when it was called Leopoldenser Turnverein (LTV), on 09/01/1885, up to the mid-40s, a moment in which the country faced a strong campaign of nationalization originated, mainly, on the Estado Novo (New State) policies (1937-945). As a theoretical-methodological reference we considered some ideas from the Cultural History. Thus, through primary written sources (documents, records, booklets, etc.) and secondary ones (books, articles) and a number of historical photographs, we analyzed some historical events produced by the Turnen in that institution. The research showed that the Turnen was the main reason for creating the LTV, being the main link with its members and other partner societies, until the end of the 30s. After this period, influenced by the nationalization policies of the Estado Novo (New State), the LTV went through a significant transformation process, which involved statutory changes and the change of its name as well. As a consequence, in 1938 it started to be called Sociedade de Ginástica de São Leopoldo (SGSL São Leopoldo Gymnastics Society). From this moment on, the links of the institution with the German values and culture, characteristics of the German immigrants still remained, however, differently from the previous period, they became less explicit and more discreet. Within the body practices it is highlighted the disappearance of the Turnen, as a gymnastics manifestation, with its own philosophy. This happened from the 40s on, concomitant with the emergence of gymnastics devices at the Sociedade de Ginástica de São Leopoldo (São Leopoldo Gymnastics Society) and with the intensification and proliferation of the sportivization of the gymnastics in Brazil and in Rio Grande do Sul (RS)